(untitled) (TRISANGAM INTERNATIONAL REFEREED JOURNAL, 2024)
Epic literature encompasses a nation’s entire geography, time, thoughts, traditions, experiences, and culture. The Ramayana, a venerable masterpiece, is a cherished gem of Indian literature. Over the course of history, it has not only impacted the mindset of people in India but also had a significant influence on the literature and culture of different parts of the globe. The Ramayana, initially written in Sanskrit, has undergone multiple reinterpretations by various poets in different regional languages of India throughout the centuries. These poets have embraced the Ramayana and adapted it to their own languages and cultures, giving it new shapes while still maintaining the fundamental plot. The scope of our study article is centred on the analysis of Chandrabati’s Ramayana, which originates from the Mymensingh district of East Bengal during the sixteenth century. Our main objective is to examine the unique characteristics of its composition. In contrast to the conventional epic framework, this narrative portrays the influence of the Ramayana on the realm of female intellect and awareness. This rendition emphasises the character of Sita, her story, and her hardships more than Rama. The Ramayana was extensively transmitted through oral tradition among the women in the Mymensingh district. Later on, the information was gathered and documented by different individuals who specialise in collecting and studying such materials. This research paper examines the poet Chandrabati and her life, the way her life is portrayed in the Ramayana narrative, the distinctiveness and originality of the story, the portrayal of love and marriage, and the significance of the narrative style of the Ramayana as written by a woman during that time period.